Socialization Dynamics and Value System Crisis in Multicultural Setting: Implication to Adult Learning and Social Policy in Nigeria Institutions of Higher Learning - Andrew N. Ogbochie; Okafor, Samuel; Kingsley A. Ogbonnaya; Ekaette Okop (Italian Sociological Review, 2025)
Value system crisis, which is behind majority of other crises in the society across the globe, can be located behind the issues of socialization crisis. This study focused on understanding and explaining the aforementioned issues among Nigerian students in the higher institutions of learning. The study involving multicultural contexts included some 2400 students from 16 institutions of higher learning and more than 30 ethnic and socio-cultural groups from across Nigeria. The study adopted survey design with questionnaire instrument from the combination of Familial Ethnic Socialization Measure (FESM), California Psychological Inventory Socialization scale (CPI-So), Parental Socialization Scale ESPA29 (English translation) and Social Value Questionnaire (SVQ) with modifications to capture the major thrust of the study and the current issues in the environment of the study. The collected data were analyzed with SPSS version 23, while percentage, correlation and regression statistics were deployed to check for relationship of variables. According to the major findings of the study, socialization dynamics [SD1] is positively correlated with value system crisis-1 [VSC-1] (p<000, r.218), but negatively correlated with VSC-2 (p<000, r-.192) and VSC-3 (p<000, r-.275). Value system crisis was predicted by gender of the students, age, study year, religion, family background, etc. (R= 0.829, F= 65.027, P= .001). The study recommends robust policy transformation in institutions of higher learning in Nigeria for strong social institution.